(3GdOQQ GdaGNQI aj eOM SjO GdOfjG hGdBNQIs
(3ChdgG (B:s
(3HGH GdJZRd hMSf GdJfRd(B: (3gGe GdLhi Hghi djdi aMjGgG bdH JYGWi ef GdCThGb CZdGgG s
(3BNQgG (B:s
(3aGddg jQRbgG CefkG hjMaXgG MaXkG hjcdDgG OCHkG hjQYGgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B5 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(506 (3O(B) s
Keywords: (3GdCOHs